Competition policy and public procurement (UN New YorkUS, 2012)
Focuses on the role of competition in public procurement. Discusses the substantive and institutional aspects of public procurement, including strategies to broaden the cricle of potential bidders, to incentivise competitive behaviours and to fight bid rigging.
Keywords: GOVERNMENT PURCHASING